Systematic Review of the Debt Requirements Literature: Its Causes and Measurement - Sanchez Hernández, Maria Janai (2025)
Technical Requirements Debt is defined as the difference between the initially stated requirements and the final software product. This study aimed to conduct a systematic literature review based on a methodology structured in three phases: definition of a search protocol, selection of relevant scientific sources, and application of inclusion and exclusion criteria, followed by a synthesis of the collected information. Research from the last five years was analyzed, considering a total of thirteen articles. The results indicate that the main causes of Technical Requirements Debt include the lack of formal documentation, pressure to meet deadlines, poor communication between the client and the development team, as well as the absence of automated tools that optimize requirements traceability, among other factors. Regarding its measurement, strategies such as cost-benefit analysis and rectification cost estimation have been proposed; however, these have not yet been validated in real-world contexts, which limits their practical applicability. In conclusion, Technical Requirements Debt represents a challenge in software engineering, directly affecting project quality and success. This work provides an updated overview that can serve as a basis for future research in the area, with the goal of developing more effective strategies for its management and possible mitigation.